Presence of Biomolecule and Other Minerals in Raw, Roasted and Boiled Horse Gram (Kulthi Seeds) - Mishra, Harsha; Pathan, Shahin (Research Advances and Challenges in Agricultural Sciences Vol. 3, 2024)
This chapter primarily focuses on accessing the chemical composition of raw, roasted and boiled Kulthi seeds (Dolichos biflrus). Horse gram (Dolichos biflorus) is one of the obscure legumes which is also known as Gahat, Kulath or Kulthi, in India and it is used as food and fodder. The seeds under investigation were procured from the local market of village Hivre of Pune District (Maharashtra), India. The seeds were roasted (sand bath 180oC, 20 mins) and boiled (Pressure cooker, 30 mins with 1:3 v/v water). The moisture, ash (and its analysis) and calcium content of the seeds were determined by Pearson [2]. Theseeds were used to study for their moisture, total ash (and its analysis), crude protein, lipid, total carbohydrates, reducing and non-reducing sugar, phosphorus, calcium, iron and crude fibre contents. The findings revealed that the total lipid content, crude fiber content, and calcium content present in raw, roasted, and boiled seeds of kulthi was quite higher than other varieties of kulthi and other legumes.